2012
DOI: 10.1016/j.drugalcdep.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of drug users who witness many overdoses: Implications for overdose prevention

Abstract: Background Programs to improve response of drug users when witnessing an overdose can reduce overdose mortality. Characteristics of drug users may be associated with the number of overdoses ever witnessed. This information could inform overdose prevention programs. Methods Participants in New York City, who were age 18 and older with heroin and/or with cocaine use in the past two months, were administered structured interviews (n = 1,184). Survey topics included overdose response, drug use behavior, treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 33 publications
3
32
0
Order By: Relevance
“…Similar to previous literature, the majority of overdoses in this study occurred in a private home and in the presence of others (Bohnert et al, 2012; Cerdá et al, 2013; Coffin and Sullivan, 2013). Despite there being no significant difference in most indicators of scene response (i.e., witnessing, performance of CPR, paramedic response), victims of fatal heroin overdose received naloxone at twice the rate of OPR overdoses (20.8% vs. 10.0%).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to previous literature, the majority of overdoses in this study occurred in a private home and in the presence of others (Bohnert et al, 2012; Cerdá et al, 2013; Coffin and Sullivan, 2013). Despite there being no significant difference in most indicators of scene response (i.e., witnessing, performance of CPR, paramedic response), victims of fatal heroin overdose received naloxone at twice the rate of OPR overdoses (20.8% vs. 10.0%).…”
Section: Discussionsupporting
confidence: 87%
“…However, prevention of overdose death by naloxone is time-sensitive and relies on bystanders witnessing the overdose event, recognizing the signs of overdose, and taking appropriate actions to prevent the impending death. Previous literature suggests that as many as 85% of heroin overdoses may be directly witnessed (Bohnert et al, 2012; Coffin and Sullivan, 2013), however the rate of witnessing in OPR overdoses has not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Because users of illicit drugs often inject where they buy drugs, and signs of distress may appear rapidly, other users or strangers may notice that a victim is in distress. These other users, however, often do not call 911 for help, perhaps fearing police intervention (Dietze et al, 2006; Tobin, Davey, & Latkin, 2005; Wagner et al, 2015), but instead they may slap or pinch the victim, give them coffee, try to make them walk, inject them with a different substance (e.g., cocaine, salt, water), administer naloxone, or attempt CPR (Baca & Grant, 2005; Bohnert, Tracy, & Galea, 2012; Wagner et al, 2015). Researchers studying inner city illicit drug use have suggested that efforts to prevent overdose (i.e., good Samaritan laws or increased access to naloxone) could focus on those persons using drugs in public or in abandoned buildings (Bohnert et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additional interventions are needed to reduce overdose deaths when opioid-dependent people are not enrolled in OST. These include making naloxone available for peer administration to reduce fatal overdose [38][39][40] and measures to reduce overdose mortality after release from prison [36], where evidence is needed urgently on effective preventive interventions. Safe injection facilities can probably reduce overdose events in those who use them, but their limited scale of operation in most of the countries that allow them suggests that these facilities will have limited impact on opioid overdose mortality at a population level [41].…”
Section: Discussionmentioning
confidence: 99%